2003
DOI: 10.1095/biolreprod.102.009910
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of Meiotic Spindle Is Controlled by Microfilaments in Mouse Oocytes1

Abstract: The completion of meiosis requires the spatial and temporal coordination of cytokinesis and karyokinesis. During meiotic maturation, many events, such as formation, location, and rotation of the meiotic spindle as well as chromosomal movement, polar body extrusion, and pronuclear migration, are dependent on regulation of the cytoskeleton system. To study functions of microfilaments in meiosis, we induced metaphase II (MII) mouse oocytes to resume meiosis by in vitro fertilization or parthenogenetic activation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 22 publications
3
66
0
1
Order By: Relevance
“…In MII, the spindle assembles with its long axis lying parallel to the overlying cortex and therefore must rotate about 90 in order to orient properly for polar body extrusion. Spindle rotation relies on actin cytoskeleton as it is disrupted by cytochalasin B treatment [Zhu et al, 2003]. Further, the fact that blebbistatin and ML-7 block spindle rotation indicates that myosin II contractility may be required for the process [Matson et al, 2006;Wang et al, 2011].…”
Section: Polar Body Extrusion: Coordination Between Cortical Membranementioning
confidence: 99%
“…In MII, the spindle assembles with its long axis lying parallel to the overlying cortex and therefore must rotate about 90 in order to orient properly for polar body extrusion. Spindle rotation relies on actin cytoskeleton as it is disrupted by cytochalasin B treatment [Zhu et al, 2003]. Further, the fact that blebbistatin and ML-7 block spindle rotation indicates that myosin II contractility may be required for the process [Matson et al, 2006;Wang et al, 2011].…”
Section: Polar Body Extrusion: Coordination Between Cortical Membranementioning
confidence: 99%
“…35,36 Similarly, disrupting the actin cytoskeleton also affects MII spindle rotation upon fertilization or parthenogenetic activation. 37 However, in oocytes treated with GM130 MO-injection, the chromosome component of the spindle, induced an "F-actin cap" in the adjacent cortical region. Clearly, GM130 depletion did not grossly distort the actin.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Ca 2þ is released from intracellular stores and activates PKC, leading to CG exocytosis (Sun 2003). New studies suggest that CG release in mature eggs is dependent on calciumdependent proteins like those in somatic cells required to undergo calcium-regulated exocytosis (Abbott & Ducibella 2001), and calmodulin-dependent kinase II (CaMKII) may act as a switch in the transduction of the calcium signal (Sun 2003).…”
Section: Cg Exocytosismentioning
confidence: 99%
“…When oocytes are treated with cytochalasin B or D, spindle rotation is inhibited. Consequently, the oocyte forms an extra female pronucleus in the ooplasm instead of extruding a second polar body (Zhu et al 2003). By using Pol-Scope (Cambridge Research & Instrumentation, Boston, MA, USA), Navarro et al (2005) also observed the inhibition of spindle rotation by cytochalasin D in mouse oocytes.…”
Section: Actin Filaments Control the Meiotic Spindle Rotation After Ementioning
confidence: 99%